"Don't Cry, You're Not a Baby!": Emotion, Role and Hierarchy in Korean Language Socialisation Practice. (6th May 2015) - Ahn, Junehui
Abstract : I examine how South Korean children learn culturally specific emotional knowledge, especially affective hierarchy and the association between emotional displays and social roles, through participation in peer talk. An analysis of children's and teachers' everyday emotional discourses shows that children, rather than passively adopting adult emotional discourses, creatively employ a range of linguistic and communicative features regarding emotions to construct their own culture‐laden emotional world. Findings articulate the role children's peer talk has in cultural reproduction and dynamic aspects of the language socialisation processes.